Trends and inequalities in women’s use of quality antenatal care, intrapartum care, and immediate postnatal care services in Ethiopia: multivariate decomposition, secondary data analyses of four demographic and health surveys over two decades (2001–2019) - David Sibbritt; Angela Dawson; Melese Girmaye Negero (BMJ Open)
Objective This study aimed to examine the trends and inequalities in women’s use of quality antenatal care (ANC), quality intrapartum care and immediate postnatal care (PNC) services, and the determinants that contributed to changes in receiving these services from 2001 to 2019 in Ethiopia using the Ethiopia Demographic and Health Surveys (EDHSs) data.Design, outcomes, setting and analysis Secondary data analyses of four waves of nationally representative EDHSs from 2005 to 2019 were conducted. We defined quality ANC as having blood pressure measurement, blood and urine tests, iron supplementation and being informed of pregnancy-related complications during ANC visits; quality intrapartum care as having health facility birth, birth assisted by skilled personnel and newborn put to the breast within 1 hour of birth and immediate PNC as having maternal and newborn PNC within 24 hours of birth. We used control charts, multivariate logistic regression decomposition analyses and equiplots to measure and analyse trends and inequalities over two decades using data from EDHSs 2005–2019.Results Over the period 2001–2019, there were increases in the percentage of quality ANC (3.7%–39.6%), intrapartum care (3.9%–43.3%) and immediate PNC (2.6%22.1%) services received. However, there were widening inequalities between these services received by women, favouring those from advantageous socioeconomic backgrounds. From 2001–2019, the largest significant increases in the percentage of women receiving quality ANC and immediate PNC services were due to changes in the distribution of sociodemographic and maternal care characteristics, while the largest significant increase in the percentage of women receiving quality intrapartum care was due to changes in the effects of these characteristics.Conclusions The healthcare system in Ethiopia should expand access to all the recommended maternal healthcare interventions to disadvantaged population subgroups. Universal coverage of quality maternal and newborn healthcare across the continuum is needed. There is also a need to promote ≥4 ANC, early initiation of ANC, girls’ and women’s education and enabling women’s economic empowerment.